Comparison of the pervaporation separation of a water-acetonitrile mixture with zeolite-filled sodium alginate and poly(vinyl alcohol)-polyaniline semi-interpenetrating polymer network membranes - Naidu, B. V. K.; Bhat, S. D.; Sairam, M.; Wali, A. C.; Sawant, D. P.; Halligudi, Shivaraj B.; Mallikarjuna, N. N.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2005)
The pervaporation (PV) separation performance of ZSM-5- and Na-Y-type zeolite-filled sodium alginate (NaAlg) membranes were compared with those of pure NaAlg and semi-interpenetrating polymer network (semi-IPN) membranes of poly(vinyl alcohol) (PVA) with polyaniline (PANI) for the dehydration of acetonitrile. The PV separation characteristics of the zeolite-filled membranes showed a dependence on the nature of the zeolites. The variation of the acidity function of the ZSM-5 zeolite had an influence on the flux and selectivity of the membranes when compared to unfilled membranes. The crosslinked membranes were characterized by differential scanning calorimetry, X-ray diffraction, scanning electron microscopy, and Fourier transform infrared spectroscopy. Increasing the PANI content of the semi-IPN network increased the separation selectivity. Among the NaAlg membranes, the plain NaAlg membrane showed the highest selectivity of 414 at 30 mass % water in the feed mixture, whereas the Na-Y- and ZSM-5 (40)-filled NaAlg membranes exhibited much lower values of selectivity, that is, 7.3 and 4.3, respectively for 30 mass % water in the feed. When the flux and selectivity data of ZSM-5 (250)-filled NaAlg membranes were compared with that of Na-Y- or ZSM-5 (40)-filled NaAlg membranes, a noticeable increase in the selectivity for the ZSM-5 (250)filled NaAlg membrane was observed, but a somewhat comparable flux was observed compared to the plain NaAlg membrane. For the first time, PANI was polymerized with PVA to yield a semi-IPN. The total flux and water flux increased systematically, whereas the selectivity decreased greatly from 251.87 to 5.95 with increasing amounts of water in the feed. (c) 2005 Wiley Periodicals, Inc.
Keywords: Diffusion; interpenetrating network (IPN); zeolites

Highly active and selective AlSBA-15 catalysts for the vapor phase tert-butylation of phenol - Vinu, A.; Devassy, Biju M.; Halligudi, Shivaraj B.; Bohlmann, W.; Hartmann, Martin (Applied Catalysis A-General, 2005)
Hexagonally ordered mesoporous AISBA-15 catalysts having n(Si)/(nA]) ratios from 7 to 215 have been synthesized hydrothermally using a cheap non-ionic block copolymer as the structure-directing agent. The obtained materials were analyzed by XRD and nitrogen adsorption to determine the structural order and the textural properties. It has been observed by Al-27 MAS NMR spectroscopy that aluminum atoms are exclusively in tetrahedral coordination for all samples except AISBA-15(7), where octahedral aluminum has been detected to some extent. Temperature-programmed desorption of pyridine showed that AISBA-15(45) has a higher number of strong acid sites as compared to other mesoporous materials such as FeMCM-41, AIMCM-41 and FcAlMCM-41. The catalyst AlSBA-15(45)showed superior performance in the acid-catalyzed tertiary butylation of phenol employing tert-butanol as the alkylation agent. A high phenol conversion of 86.3% is observed for this catalyst at a reaction temperature of 150 degrees C. Over AISBA-15(45), the 4-TBP yield amounts to 40.5% and the 2,4-DTBP yield corresponds to 37.9%. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Acidity; AlSBA-15; aluminum incorporation; butylation of phenol; SBA-15

Liquid-phase alkylation of phenol with long-chain olefins over WOx/ZrO2 solid acid catalysts - Sarish, S.; Devassy, Biju M.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2005)
The liquid-phase alkylation of phenol with 1-dodecene was carried out over WOx/ZrO2 solid acid catalysts. The catalysts were prepared by wet impregnation method using zirconium oxyhydroxide and ammonium metatungstate. Catalysts with different WO3 loading (5-30 wt.%) were prepared and calcined at 800 degrees C and catalyst with 15% WO3 was calcined from 700-850 degrees C. All the catalysts were characterized by surface area, XRD, and FTIR. The catalyst with 15% WO3 calcined at 800 degrees C (15 WZ-800) was found to be the most active in the reaction. The effect of temperature, molar ratio and catalyst weight on dodecene conversion and products selectivity was studied in detail. Under the optimized reaction conditions of 120 degrees C, phenol/1-dodecene molar ratio 2 and time 2 h, the catalyst 15 WZ-800 gave > 99% dodecene conversion with 90% dodecylphenol selectivity. Comparison of the catalytic activity of 15 WZ-800 with sulfated zirconia calcined at 500 degrees C (SZ-500) and HP zeolite showed that activity of SZ-500 was lower than that of 15 WZ-800, while HP zeolite showed negligible activity. It is observed that the presence of water in the reaction mixture was detrimental to the catalytic activity of WOx/ZrO2. The catalyst 15 WZ-800 also found to be an efficient catalyst for alkylation of phenol with long-chain olefins like 1-octene and 1-decene. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Alkylation; long-chain olefins; phenol; tungsten oxide; Zirconia

Miscibility of chitosan-hydroxyethylcellulose blends in aqueous acetic acid solutions at 35 degrees C - Wali, A. C.; Naidu, B. V. K.; Mallikarjuna, N. N.; Sainkar, S. R.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2005)
The miscibility of blends of chitosan and hydroxyethylcellulose in a 2% acetic acid solution was studied by viscometry, densitometry, and refractometry at 35 degrees C. The data suggest that the blends were completely miscible in all proportions. Further, the membranes were fabricated from concentrated blend solutions. The solid-state compatibility of the blends was confirmed by scanning electron microscopy. (c) 2005 Wiley Periodicals, Inc.
Keywords: blends; miscibility; refractive index; viscosity

Silicotungstate-modified zirconia as an efficient catalyst for phenol tert-butylation - Devassy, Biju M.; Shanbhag, G. V.; Mirajkar, Subhash P.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2005)
The alkylation of phenol with tert-butanol was investigated using zirconia modified with silicotungstic acid (STA) as catalysts. The catalysts with different STA loading (5-25 wt.% calcined at 750 degrees C) and calcination temperature (15 wt.% calcined from 350 to 850 degrees C) were prepared and characterized by X-ray diffraction and NH3-TPD measurements. The XRD results indicate that STA stabilizes the tetragonal phase of zirconia. The catalyst with 15% STA on ZrO2 calcined at 750 degrees C shows the highest acidity and hence highest activity. Under the reaction conditions of 140 degrees C, tert-butanol/phenol molar ratio of 2 and LHSV of 4 h(-1), phenol conversion was 95.4% with selectivity to 2-tert-butyl phenol 4.3%, 4-tert-butyl phenol 59.2% and 2,4-di-tert-butyl phenol 35.8%. The reaction was studied as a function of time for 50 It without appreciable change in phenol conversion and product selectivity. The deactivated catalyst could be regenerated by calcination with out appreciable lose in catalytic activity and product selectivity. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: phenol; Silicotungstic acid; tert-butylation; Zirconia

Synthesis of linear alkyl benzenes over zirconia-supported 12-molybdophosphoric acid catalysts - Devassy, Biju M.; Lefebvre, F.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A - Chemical, 2005)
The liquid-phase alkylation of benzene with 1-octene and 1-dodecene was investigated using zirconia-supported 12-molybdophosphoric acid (MPA) as catalyst. The catalysts with different MPA loading (5-25 wt.% calcined at 700 degrees C) and calcination temperature (15 wt.% calcined from 500 to 750 degrees C) were prepared by suspending zirconium oxyhydroxide in methanol solution of MPA followed by drying and calcination. These catalysts were characterized by X-ray diffraction, and P-31 MAS NMR spectroscopy measurements. The XRD results indicated that MPA stabilizes the tetragonal phase of zirconia. 3 1 P MAS NMR spectra show that the nature of phosphorous species depend on MPA loading and calcination temperature, and it show the existence of three types of phosphorous species, one is the Keggin unit and the other is the decomposition product of MPA and third one an unidentified species. FTIR pyridine adsorption on 15% MPA catalyst calcined at 700 degrees C showed the presence both Bronsted and Lewis acidity. Under the reaction conditions of 83 C, benzene/1-olefin molar ratio of 10 (time, 1 h), the most active catalyst, 15% MPA calcined at 700 C gave more than 90% olefin conversion with selectivity to 2-phenyl octane, 55% and 2-phenyl dodecane, 45%. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 12-molybdophosphoric acid; benzene alkylation; linear alkyl benzene; Zirconia

tert-Butylation of p-cresol over WOx/ZrO2 solid acid catalysts - Sarish, S.; Devassy, Biju M.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A - Chemical, 2005)
The tert-butylation of p-cresol with tert-butanol was carried out over WO3/ZrO2 catalysts under flow conditions, The catalysts were prepared by wet impregnation method using zirconium oxyhydroxide and ammonium metatungstate. Catalysts with different WO3 loading (5-30 wt.%) were prepared and calcined at 800 degrees C and catalyst with 15% WO,, was calcined from 600 to 900 C. The catalysts were characterized by surface area, XRD, FTIR and TEM. The catalyst 15% WO3/ZrO2 calcined at 800 degrees C found to be the most active in the reaction. The effect of temperature, space velocity and molar ratio of the reactants on the conversion of p-cresol and products selectivities were studied. Under the optimized reaction conditions of 130 degrees C, tert-butanol/p-cresol molar ratio of 3 and flow rate of 10 ml h(-1). p-cresol conversion was 69.8% with selectivity to 2-tert-butyl-p-cresol 92.4%, 2,6-di-tert-butyl-p-cresol 6.3% and p-cresol tert-butyl ether 1.3%. The catalytic activity is compared with sulfated zirconia, USY, H beta zeolites and montmorillonite K-10 under the optimized reaction conditions The activity of sulfated zirconia is lower than that of 15% WO3/ZrO2 catalyst calcined at 800 C and other catalysts showed very low activity, (c) 2005 Elsevier B.V.. All rights reserved.
Keywords: p-Cresol; tert-butylation; tungsten oxide; Zirconia

Zirconia-supported 12-tungstophosphoric acid as a solid catalyst for the synthesis of linear alkyl benzenes - Devassy, Biju M.; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2005)
The liquid-phase alkylation of benzene with 1-octene and 1-dodecene was investigated with zirconia-supported 12-tungstophosphoric acid (TPA) as catalysts. We prepared the catalysts, with different TPA loading (5-20 wt% calcined at 750 degrees C) and calcination temperatures (15 wt% calcined from 650 to 850 degrees C), by suspending hydrous zirconia in a methanol solution of TPA, followed by drying and calcination. These catalysts were characterized by X-ray diffraction, DTG-DTA, FTIR pyridine adsorption, NH3-TPD, and P-31, MAS NMR spectroscopy measurements. The catalyst with optimum TPA loading (15%) and calcination temperature (750 degrees C) was prepared in different solvents and characterized by P-31 MAS NMR spectroscopy. The XRD results indicate that TPA stabilizes the tetragonal phase of zirconia. The catalysts show both Bronsted and Lewis acidity, and 15% TPA on zirconia calcined at 750 degrees C shows the highest acidity. P-31 MAS NMR spectra show two types of phosphorous species: one is the Keggin unit and the other is the decomposition product of TPA. The relative amount of each depends on TPA loading, calcination temperature, and the solvent used for the catalyst preparation. Under reaction conditions of 84 degrees C and a benzene/1-olefin molar ratio of 10 (time 1 h), the most active catalyst, 15% TPA, calcined at 750 degrees C, gave more than 98% olefin conversion with selectivity for 2-phenyl octane (53.5%) and 2-phenyl dodecane (47%). (c) 2004 Elsevier Inc. All rights reserved.
Keywords: 12-tungstophosphoric acid; linear alkyl benzene; solvent effect; Zirconia

Zirconia-supported phosphotungstic acid as catalyst for alkylation of phenol with benzyl alcohol - Devassy, Biju M.; Shanbhag, G. V.; Lefebvre, F.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A - Chemical, 2005)
The liquid-phase alkylation of phenol with benzyl alcohol was carried out using zirconia-supported phosphotungstic acid (PTA) as catalyst. The catalysts with different PTA loadings (5-20 wt.% calcined at 750 degrees C) and calcination temperature (15 wt.% calcined from 650 to 850 degrees C) were prepared and characterized by (31)p MAS NMR and FT-IR pyridine adsorption spectroscopy. The catalyst with optimum PTA loading (15%) and calcination temperature (750 degrees C) was prepared in different solvents. 31p MAS NMR spectra of the catalysts showed two types of phosphorous species, one is the Keggin unit and the other is the decomposition product of PTA and the relative amount of each depends on PTA loading, calcination temperature and the solvent used for the catalyst preparation. The catalysts with 15% PTA on zirconia calcined at 750 degrees C showed the highest Bronsted acidity. At 130 degrees C and phenol/benzyl alcohol molar ratio of 2 (time, I h), the most active catalyst, 15% PTA calcined at 750 degrees C gave 98% benzyl alcohol conversion with 83% benzyl phenol selectivity. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Benzylation; phenol; Phosphotungstic acid; Zirconia

Adsorption of methanol on Si(100)/SiO(2)and mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Mathew, Nevin T.; Ravi, V.; Jacob, Nalini E.; Patil, K. R. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2006)
Adsorption of methanol on SiO(100)/SiO2 substrate and mesoporous SBA-15 has been studied by using Fourier transform infrared (FTIR) and X-ray photoelectron spectroscopy (XPS). Contact angle technique is employed to study the adsorption kinetics of methanol on SiO(100)/SiO2 and thermal stability of adlayer. Thermogravimetric (TGA) technique is used to understand the thermal behavior of methanol layer on SBA-15. Adsorption kinetics fit fairly well with Langmuir isotherms giving adsorption rate constant, k(a) = 0.0021 W s(-1). FTIR results show formation of methoxy silicon (SiOCHA silicon polyhydride (SiH2), carboxylate, molecular water and hydroxyl groups on Si(100)/SiO2 surface and only methoxy silicon on SBA-15. XPS results confirm methanol adsorption and support FTIR results. The methanol adlayers are found to be thermally stable up to a temperature of similar to 262 degrees C on both Si(100)/SiO2 and SBA-15 and decompose between 262 and 450 degrees C. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Adsorption; desorption; kinetics; Methanol; SBA-15; Si(100)/SiO2; thermal stability

Adsorption of octadecyltrichlorosilane on mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Sawant, Dhanashri P.; Jacob, Nalini E.; Patil, K. R.; Gaikwad, A. B.; Pradhan, S. D. (Applied Surface Science, 2006)
Adsorption of octadecyltrichlorosilane (OTS) on mesoporous SBA-15 has been studied by using Brunauer-Emmett-Teller (BET) surface area analysis, scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDAX), Fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS) and thermo-gravimetric analysis (TGA) techniques. BET surface area analysis shows decrease of surface area from 930 to 416 m(2)/g after OTS adsorption. SEM pictures show close attachment of SBA-15 particles. EDAX measurements show increase of carbon weight percentage and decrease of oxygen and silicon weight percentage. XPS results closely support EDAX analysis. FTIR spectra shows presence of methyl (-CH3) and methylene (-CH2) bands and oriented OTS monolayer on SBA-15. Thermo-gravimetric analysis shows that the OTS adsorbed on SBA-15 are stable up to a temperature of 230 degrees C and that the OTS monolayers decompose between 230 and 400 degrees C. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Adsorption; OTS; SBA-15; Self-assembly; thermal stability

Effect of calcination temperature on the catalytic activity of zirconia-supported heteropoly acids - Devassy, Biju M.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2006)
Zirconia-supported silicotungstic acid (15% STA) catalyst with different calcination temperatures (600-850 degrees C) was prepared by suspending zirconium oxyhydroxide in methanol solution of STA followed by drying and calcination. These catalysts were characterized by XRD, FTIR pyridine adsorption and DRUV-vis spectroscopy. The catalysts showed both Bronsted as well as Lewis acidity and 15% STA on zirconia calcined at 750 degrees C (15 SZ-750) had the highest Bronsted acidity. Characterization of 15 SZ-750 catalyst by Raman spectroscopy showed the presence of zirconia-anchored mono-oxotungstate as the major tungsten species present in this catalyst. These catalysts were used in benzoylation of veratrole with benzoic anhydride and 15 SZ-750 catalyst showed the highest activity. For catalyst with support calcined at different temperatures before HPA impregnation, catalytic activity decreases as the support calcination temperature increases due to the decrease in Bronsted acidity. Comparison of the catalytic activity of 15 SZ-750 with that of zirconia-supported phosphotungstic acid (15%, calcined at 750 degrees C, 15 PZ-750) in benzoylation of veratrole with benzoic anhydride, acylation of anisole with acetic anhydride and in alkylation of diphenylether with 1-dodecene showed that 15 SZ-750 catalyst has higher activity and deactivation resistance due to its higher Bronsted acidity. The deactivated catalyst could be regenerated by calcination without appreciable loss in activity. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Acylation; Alkylation; Anisole; diphenylether; Phosphotungstic acid; Silicotungstic acid; veratrole; Zirconia

Heteropoly acid supported on titania as solid acid catalyst in alkylation of p-cresol with tert-butanol - Kumbar, Suresh M.; Shanbhag, G. V.; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2006)
Butylation of p-cresol with tert-butanol was investigated on titania modified with 12-tungstophosphoric acid (TPA/TiO2) catalyst under vapor phase conditions. Catalysts with different TPA loadings (10-25 wt.%) and calcination temperatures (650-750 degrees C) were prepared by suspending titanium hydroxide in methanol solution of TPA followed by drying and calcination. These catalysts were characterized by surface area, XRD, P-31 MAS NMR, XPS, NH3-TPD, and FTIR pyridine adsorption. XRD results indicated that the presence of TPA retarded the crystallization of titania and stabilized TiO2 in anatase phase. P-31 MAS NMR indicated the presence of TPA in various forms (dispersed, highly fragmented and Keggin intact). These catalysts showed both Bronsted and Lewis acidity, and 20% TPA on TiO2 calcined at 700 degrees C (from here after words 20% TT 700) had the highest Bronsted as well as total acidity. Further, the catalytic activities were examined in tert-butylation of p-cresol with tent-butanol. The catalytic activity depended on TPA coverage, and the highest activity corresponded to the monolayer of TPA on titania. The most active catalyst 20% TT-700 gave 82% conversion of p-cresol and 89.5% selectivity towards 2-tert-butyl cresol (TBC), 2,6-di-tert-butyl cresol (DTBC) 7.5% and cresol-tert-butyl ether (CTBE) 3% under optimized conditions. The activity was always higher than that of WO3/ZrO2, sulfated zirconia (SZ), USY, H-beta zeolites and montmorillonite K-10 (K-10mont) under similar conditions. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 2; 2-tert-butyl-p-cresol; 6-di-tert-butyl-p-cresol; Alkylation; heteropoly acid; p-Cresol; tert-butanol; titania

Mesoporous molecular sieve (MCM-41)-filled sodium alginate hybrid nanocomposite membranes for pervaporation separation of water-isopropanol mixtures - Bhat, S. D.; Naidu, B. V. K.; Shanbhag, G.; Halligudi, Shivaraj B.; Sairam, M.; Aminabhavi, Tejraj M. (Separation of Purification Technology, 2006)
Sodium alginate (NaAlg) and the inesoporous molecular sieve (MCM-41)-filled NaAlg nanocomposite membranes have been prepared by solution casting and crosslinked with glutaraldehyde. Pervaporation performance of the MCM-41-filled NaAlg membranes has been tested and compared with plain NaAlg membrane for dehydrating isopropanol at 30 degrees C. In the studied feed composition range of 10-50 mass% of water, 20 mass% MCM-41-loaded NaAlg membrane gave the highest selectivity ranging between 29,991 and 3332 in the range of feed water compositions of 10-50 mass%. Flux for the plain NaAlg membrane ranged between 0.067 and 0.340 kg/(m(2)h), while for 20 mass% MCM-41-filled NaAlg membrane, flux increased to 0.110 and 0.555 kg/(m(2)h). To the best of our knowledge, this is the first study reported on the membrane forming properties of an admixed hybrid composite of a mesoporous molecular sieve (MCM-41) with NaAlg used in dehydration of isopropanol, yielding high selectivity to water at higher loadings of the molecular sieve as a filler. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: flux and selectivity; nanocomposite membranes; pervaporation; sodium alginate; water-isopropanol

Shape selective synthesis of long-chain linear alkyl benzene (LAB) with AIMCM-41/beta zeolite composite catalyst - Bordoloi, Ankur; Devassy, Biju M.; Niphadkar, P. S.; Joshi, P. N.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2006)
The liquid-phase alkylation of benzene with long-chain olefins such as 1-decene, 1-octene and 1-dodecene was carried out over AIMCM-41/Beta zeolite composite material as catalyst. The catalyst was prepared by seeding method and characterized by XRD, N-2 sorption, FTIR pyridine adsorption, NH3-TPD and SEM. Powder XRD of AlMCM-41/Beta zeolite composite material showed the co-existence of well-structured microporous and mesophase of AlMCM-41. The typical textural characteristics of micro- and meso-structured phases were observed in the composite material. The effect of temperature, reactant molar ratios and catalyst weight on 1-dodecene conversion and products selectivity was studied. The composite catalyst was found to be the highly selective towards the formation 2-dodecylbenzene. Under the reaction conditions of 120 degrees C, benzene/1-dodecene molar ratio 10 and time 2h, the catalyst gave 48% dodecene conversion with 76%, 2-dodecylbenzene selectivity. Significant improvement in catalytic activity has been achieved by composite material as compared to Al-MCM-41. Although zeolite beta and composite material gave similar conversion of dodecene, the composite material showed higher selectivity towards 2-dodecylbenzene, which could be due to higher diffusibility of 2-dodecylbenzene isomer in the composite material. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: AIMCM-41/beta zeolite composite; Alkylation; Benzene; long-chain olefins

Synthesis, characterization, and molecular modeling studies of novel polyurethanes based on 2,2 '-[ethane-1,2-diylbis(nitrilomethylylidene)]diphenol and 2,2 '-[hexane-1,6-diylbis(nitrilomethylylidene)]diphenol hard segments - Raghu, A. V.; Gadaginamath, G. S.; Jawalkar, S. S.; Halligudi, Shivaraj B.; Aminabhavi, T. A. (Journal of Polymer Science Part A-Polymer Chemistry, 2006)
Novel polyurethanes (PUS) based on 2,2 `-[ethane-1,2-diylbis(nitrilomethylylidene)]diphenol and 2,2 `-[hexane-1,6-diylbis(nitrilomethylylidene)]diphenol as hard segments containing four aromatic diisocyanates (4,4 `-diphenylmethane diisocyanate, toluene 2,4-diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate) have been prepared. Fourier transform infrared, UV spectrophotometry, fluorescence spectroscopy, H-1 NMR and C-13 NMR spectroscopy, thermogravimetric analysis, and differential thermal analysis have been used to determine the structural characterization and thermal properties of the segmented PUS. All the PUS contain domains of both semicrystalline and amorphous structures, as indicated by X-ray diffraction. The acoustic properties have been calculated with the group contribution method. Molecular dynamics simulations have been performed on all the PUS to estimate the cohesive energy density and solubility parameter values, which compare well with the values calculated with the group contribution method. Furthermore, the simulation protocols have been applied to the PUS to produce X-ray diffraction plots to determine the phase morphology of the PUS. The surface properties of the PUS have been estimated from the simulation protocols. (c) 2006 Wiley Periodicals, Inc.
Keywords: amorphous; hard segments; molecular dynamics; Morphology; polyurethanes; Schiff base containing polymers; Thermal properties

Adsorption of methanol on mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Mathew, Nevin T.; Jacob, Nalini E.; Patil, K. R.; Gaikwad, A. B. (Materials Letter, 2007)
The adsorption of methanol onmesoporous SBA-15 has been studiedbyrising Brunauer-Emmett-Teller (BET) surface area analysis, scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, X-ray photoclectrom spectroscopy (XPS) and tbennogravimettic analysis (TGA). The BET surface area analysis shows decreases of the surface area from 387 to 383 m(2)/g, pore volume from 0.88 to 0.81 cm(3)/g and pore diameter from 9.07 to 8.4 mm after methanol adsorption. The appearance of strong IR bands at 2862 and 2964cm(-1) due to methyl (-CH3) symmetric and asymmetric stretching demonstrate the presence of methanol and evidence of successful methanol adsorption. XPS results show increase of carbon and oxygen content on the surface of SBA-15. Thermogravirriettic analysis shows that the methanol adsorbed on SBA-15 is stable up to a temperature of 265 degrees C and that the methanol adlayers decompose between 265 and 588 degrees C. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Electron microscopy; Methanol; SBA-15; Surfaces; thermal stability

Au-Pt nanoparticles in amine functionalized MCM-41: catalytic evaluation in hydrogenation reactions - Joseph, Trissa; Kumar, K. Vijay; Ramaswamy, A. V.; Halligudi, Shivaraj B. (Catalysis Communications, 2007)
Nano-sized Au-Pt nanoparticles (Au-Pt-bi-MNPs) have been synthesized by the simultaneous reduction of HAuCl4 and HPtCl6 by NaBH4 inside the channels of amine functionalized Si-MCM-41 (NH2-Si-MCM-41) at ambient conditions. These materials were characterized using chemical analysis, UV-vis, XPS, XRD, FT-IR, Surface area and TEM analysis. The size of these alloyed nanoparticles (bi-MNPs) were found in the range of 2-4 nm. These nanoparticles were evaluated to study their catalytic activities towards hydrogenation of aromatic nitro compounds. The catalytic activity of the Au-Pt bi-MNPs was found to be superior to monometallic An nanoparticles. (c) 2006 Published by Elsevier B.V.
Keywords: amine-functionalized MCM-41; Au-Pt nanoparticles; Catalytic hydrogenation

Catalytic performances of silicotungstic acid/zirconia supported SBA-15 in an esterification of benzyl alcohol with acetic acid - Sawant, Dhanashri P.; Vinu, A.; Justus, Josena; Srinivasu, P.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2007)
Liquid phase esterification of benzyl alcohol (BA) to benzyl acetate (Peach fragrance) with an acetic acid (AA) has been investigated with 12-silicotungstic acid supported on zirconia embedded inside SBA-15 (STA/ZrO2/SBA- 15) as the catalyst. Catalysts were unambiguously characterized by XRD, N-2 adsorption-desorption, FF-IR pyridine adsorption techniques and the total amount of acidity of different STA loaded catalysts was estimated by TPD of NH3. The optimization of reaction conditions of an esterification of BA with AA was performed with 15 wt.% STA/22.4 wt.% ZrO2/SBA-15 calcined at 1123 K by varying catalyst concentration (1-10 wt.% of reaction mixture); temperature, 353-383 K and AA:BA molar ratio as 0.5-3. The 15 wt.% STA/22.4 wt.% ZrO2/SBA-15 calcined at 1123 K was found to have the highest acidity and more active in the reaction. Under the optimized reaction conditions, the 15 wt.% STA/22.4 wt.%ZrO2/SBA-15 calcined at 1123 K gave 59% BA conversion with selectivity for benzyl acetate as high as 96% within 2 h of reaction time. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: 12-silicotungstic acid; Benzyl acetate; Benzyl alcohol; Esterification; SBA-15

Copper(II) ion exchanged A1SBA-15: a versatile catalyst for intermolecular hydroamination of terminal alkynes with aromatic amines - Shanbhag, Ganapati V.; Joseph, Trissa; Halligudi, Shivaraj B. (Journal of Catalysis, 2007)
The hydroarnination reaction offers a very attractive route for the synthesis of alkylated amines and their derivatives with no byproduct formation. AISBA-15 was synthesized by isomorphous substitution of aluminum into the framework of SBA-15, which induces the Bronsted acid sites, and these were exchanged with metal ions such as Cu2+, Zn2+, and Pd2+. The catalysts were characterized by XRD, N-2-sOrption, SEM, TEM, acidity measurements by FT-IR pyridine adsorption, H-2-TPR, (27)AI MAS NMR, and Si-29 MAS NMR. Hydroamination of phenylacetylene (PhAc) with 2,4-xylidine has been used as a test reaction, which gave N-(1-phenylethylidene)-2,4-dimethylaniline with no byproduct formation. CuAlSBA-15 and CuAIMCM-41 showed around three times greater activity in hydroamination of PhAc compared with Cu-clay and Cu-beta, due to the moderate Lewis acidity of Cu2+ present in mesoporous supports. The performance of the CuAlSBA-15 was also determined with different alkynes and amines to evaluate the catalyst's general applicability in hydroamination reactions. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: A1SBA-15; addition; alkyne; Amine; Copper catalyst; heterogeneous; hydroamination; ion exchange; Mesoporous

Development of transdermal drug-delivery films with castor-oil-based polyurethanes - Shelke, Namdev B.; Sairam, Malladi; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2007)
Two different types of polyurethanes (PUs) were prepared with castor oil, ethylene glycol, isophorene diisocyanate and castor oil, and isophoren diisocyanate and poly(ethylene glycol) (400 or 600). PU films were prepared and characterized by Fourier transform infrared spectroscopy, differential scanning calorimetry, and gel permeation chromatography. We prepared transdermal patches by loading different amounts of drug, plasticizer, and penetration enhancer. In vitro drug permeability through the castor-oil-based aliphatic PU patches was examined with a Keshary-Chien diffusion cell. The effect of castor oil on the film-forming properties and the effect of penetration enhancers on diffusion characteristics of indomethacin (IDM) drug through the castor-oil-based PU were investigated. Prolonged release of IDM was observed from the prepared PU patches. In vitro drug diffusion revealed that slow and prolonged release of IDM was achieved in the absence of penetration enhancers. The use of penetration enhancers showed a significant effect on drug diffusion. (c) 2006 Wiley Periodicals, Inc.
Keywords: castor oil; drug delivery; polyurethane; transdermal

Effect of pretreatment conditions on the catalytic activity of nano-sized TPA/ZrO2 dispersed in SBA-15 channels in acetylation reactions - Sawant, Dhanashri P.; Hartmann, Martin; Halligudi, Shivaraj B. (Microporous and Mesoporous Materials, 2007)
Acetylation of an aromatic compounds such as veratrole (1,2-dimethoxybenzene), anisole, thioanisole, isobutyl benzene and 2-methoxynaphthalene with acetic anhydride has been investigated over a nano-sized 12-tungstophosphoric acid (TPA)/22.4 wt.%ZrO2/SBA- 15 catalysts in the liquid phase conditions. Catalysts with different (%) TPA and zirconia loadings calcined at different temperatures were prepared by wet-impregnation and characterized by XRD, N-2 adsorption-desorption, FT-Rarnan, X-ray photoelectron spectroscopy (XPS). The acidic behavior of the catalyst was studied by TPD of ammonia and FT-IR pyridine adsorption. Among the catalysts, 15 wt.%TPA/22.4 wt.%ZrO2/SBA- 15 calcined at 1123 K had the highest acidity and was the most active catalyst in veratrole acetylation with acetic anhydride. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: acetylation; SBA-15; TPA/ZrO2; veratrole; wet-impregnation

One-step synthesis of SBA-15 containing tungsten oxide nanoclusters: a chemoselective catalyst for oxidation of sulfides to sulfoxides under ambient conditions - Bordoloi, Ankur; Vinu, Ajayan; Halligudi, Shivaraj B. (Chemical Communications, 2007)
Tungsten oxide nanoclusters supported highly ordered mesoporous SBA-15 material has been successfully synthesized in a single step using a non-ionic surfactant as a template and used for the selective oxidation of sulfur compounds, giving excellent yields at room temperature with exceptional catalyst recyclability.

Organotin-oxometalate coordination polymer catalyzed oxyfunctionalization of monoterpenes - Bordoloi, Ankur; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2007)
Keywords: Heck reaction; kinetics; Palladacycle

Oxyfunctionalisation of adamantane using inorganic-organic hybrid materials based on isopoly and heteropoly anions: kinetics and mechanistic studies - Bordoloi, Ankur; Vinu, Ajayan; Halligudi, Shivaraj B. (Applied Catalysis A-General, 2007)
{Oxyfunctionalisation of adamantane with 30% aq.H2O2 in butyronitrile solvent was efficiently catalyzed by inorganic-organic hybrid materials synthesized by the immobilisation of isopoly (WOx = sodium tungstate
Keywords: adamantane; inorganic-organic hybrid materials; oxyfunctionalisation; vanadium (V) superoxo intermediate

Preparation and evaluation of cellulose acetate butyrate and poly(ethylene oxide) blend microspheres for gastroretentive floating delivery of repaglinide - Rokhade, Ajit P.; Patil, Sangamesh A.; Belhekar, Anagha A.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2007)
In this study, hollow microspheres of cellulose acetate butyrate (CAB) and poly(ethylene oxide) (PEO) were prepared by emulsion-solvent evaporation method. Repaglinide was successfully encapsulated into floating microspheres. Various formulations were prepared by varying the ratio of CAB and PEO, drug loading and concentration of poly(vinyl alcohol) (PVA) solution. Encapsulation of the drug up to 95% was achieved. The microspheres tend to float over the simulated gastric media for more than 10 h. The micromeritic properties of microspheres reveal the excellent flow and good packing properties. The % buoyancy of microspheres was found to be up to 87. SEM showed that microspheres have many pores on their surfaces. Particle size ranges from 159 to 601 mu m. DSC and X-RD revealed the amorphous dispersion in the polymer matrix. In vitro release experiments were performed in simulated gastric fluid. In vitro release studies indicated the dependence of release rate on the extent of drug loading and the amount of PEO in the microspheres; slow release was extended up to 12 h. The release data were fitted to an empirical equation to compute the diffusional exponent (n), which indicated that the release mechanism followed the non-Fickian trend. (C) 2007 Wiley Periodicals, Inc.
Keywords: cellulose acetate butyrate; Controlled release; floating drug delivery; microspheres; repaglinide

Selective oxidation of anthracene using inorganic-organic hybrid materials based on molybdovanadophosphoric acids - Bordoloi, Ankur; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2007)
{Inorganic-organic hybrid materials were synthesized by immobilization of molybdovanadophosphoric acids onto mesoporous silicas, such as MCM-41, MCM-48, and SBA-15, through an organic linker. 12-Molybdovanadophosphoric acids of the general formula H3+xPMO12-xVxO40 (x = 0-3).nH(2)O, such as H-4[
Keywords: EPDM; Photostabilization; polymeric HALS

Synthesis and characterization of novel polyurethanes based on 4,4 `-[1,4-phenylenedi-diazene-2,1-dlyl] bis(2-carboxyphenol) and 4,4 `-[1,4-phenylenedi-diazene-2,1-diyl] bis(2-chlorophenol) hard segments - Raghu, A. V.; Gadaginamath, G. S.; Mathew, Nevin T.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Reactive & Functional Polymers, 2007)
Eight novel polyurethanes (PUs) based on 4,4'-[1,4-phenylenedi-diazene-2,1-diyl]bis(2-carboxyphenot) and 4,4'-[1,4phenylenedi-diazene-2,1-diyl]bis(2-chloro- phenol) as hard segments with four diisocyanates viz., 4,4-diphenyl-methane diisocyanate, toluene 2,4-diisocyanate, isophorone diisocyanate and hexamethylene diisocyanate were prepared. Structural and thermal characterization of the segmented PUs were determined by FT-IR, UV spectrophotometry, fluoroscence spectroscopy, H-1 NMR, C-13 NMR spectroscopy and DTA/TGA analysis. All the PUs contain domains of semi-crystalline and amorphous structures, as indicated by X-ray diffraction. PUs were soluble in polar aprotic solvents like N-methyl-2-pyrrolidone (NMP), dimethyl formamide (DMF) and dimethylsulfoxide (DIVISO). (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: azo polymers; fluorescence; hard segments; Morphology; phase separation; polyurethanes; spectroscopy; Thermal properties

Synthesis, characterization, and acoustic properties of new soluble polyurethanes based on 2,2 `-[1,4-phenylenebis(nitrilomethylylidene)diphenol and 2,2 `-[4,4 `-methylene-di-2-methylphenylene-1,1 `-bis(nitrilomethylylidene)]diphenol - Raghu, A. V.; Gadaginamath, G. S.; Mathew, Nevin T.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2007)
Eight novel polyurethanes based on 2,2'-[1,4-phenylenebis(nitrilomethylylidene)]diphenol and 2,2-[4,4'methylene-di-2-methylphenylene-1,1'-bis(nitrilomethylylidene) ]diphenol acting as hard segments with two aromatic and two aliphatic diisocyanates (4,4'-diphenytmethane diisocyanate, toluene 2,4-diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate) were prepared and characterized with Fourier transform infrared, UV spectrophotometry, fluorescence spectroscopy, H-1-NMR and C-13-NMR spectroscopy, thermogravimetric analysis, and differential thermal analysis. All the polyurethanes contained domains of semicrystalline and amorphous structures, as indicated by X-ray diffraction. The acoustic properties and solubility parameters were calculated with the group contribution method. (c) 2007 Wiley Periodicals, Inc.
Keywords: infrared spectroscopy; NMR; phase behavior; polyurethanes; Thermal properties

Tungstophosphoric acid and zirconia supported on mesoporous silica catalyst in veratrole acetylation - Halligudi, Shivaraj B. (From ZEOLITES to Porous Mof Materials: The 40th Anniversary of International ZEOLITE Conference, Proceedings of The 15th International ZEOLITE Conference, 2007)
Tungstophosphoric acid (TPA) over zirconia dispersed uniformly in mesoporous silica (MS) channels of MCM-41 and MCM-48 was synthesised and tested for its catalytic activity in veratrole acetylation. Catalysts with different TPA loadings (5 to 50 wt.%) on 22.4 wt.% ZrO(2)/MCM-41 and 15 wt.% TPA on different zirconia loadings (10-70 wt.%)/MCM-41 were prepared and calcined at 1123 K. Catalysts were characterised by known techniques. Mesoporous silica supports play an important role in stabilising catalytically active TPA along with tetragonal phase of zirconia. Among the catalysts, 15 wt.% TPA/22.4 wt.% ZrO(2)/MCM-41 calcined at 1123 K was found to have the highest acidity and be at least four times more active than neat 15 wt.% TPA/ZrO(2) in veratrole acetylation to acetoveratrone by acetic anhydride.

Tungstophosphoric acid supported on titania: a solid acid catalyst in benzylation of phenol with benzylalcohol - Kumbar, Suresh M.; Halligudi, Shivaraj B. (Catalysis Communictions, 2007)
{Benzylation of phenol with benzylalcohol was carried out in liquid phase over tungstophosphoric acid (TPA) supported on titania. The catalysts were prepared with different TPA (10-25%) loading by wet impregnation method, were calcined at 700 degrees C and characterized by XRD, surface area, FTIR and acidity of the catalysts was measured by temperature programmed desorption of NH(3)-TPD, FTIR pyridine adsorption. The catalysts have been represented by a general formula as xPTiO(2)-Y (where x = wt%
Keywords: benzyl ether; benzyl phenol; benzylalcohol; Heteropolyacid; phenyl benzyl ether; titania; tungstophosphoric acid

Tungstophosphoric acid supported over zirconia in mesoporous channels of MCM-41 as catalyst in veratrole acetylation - Sawant, Dhanashri P.; Vinu, A.; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2007)
Tungstophosphoric acid (TPA) over zirconia dispersed uniformly in mesoporous silica (MS) channels of MCM-41 and MCM-48 were synthesized and tested for their catalytic activity in veratrole acetylation. Catalysts with different TPA loadings (5-50 wt.%) on 22.4 wt.%ZrO2/MCM-41 and 15 wt.%TPA on different zirconia loadings (10-70 wt.%)/MCM-41 were prepared and calcined at 1123 K. The physico-chemical characterization of the supported catalysts was done by powder X-ray diffraction (XRD), surface area measurement (BET), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transformed-infrared (FT-IR) spectroscopy, UV-vis diffuse reflectance spectra, Temperature programmed desorption (TPD) of ammonia, FT-IR pyridine adsorption and (31) P cross polarization-magic angle spinning (CP-MAS) NMR spectroscopy. The mesoporous silica supports play an important role in stabilizing catalytically active TPA along with tetragonal phase of zirconia. Among the catalysts, 15 wt.%TPA/22.4 wt.%ZrO2/MCM-41 calcined at 1123 K was found to have highest acidity and at least four times more active than neat 15 wt.%TPA/ZrO2 in veratrole acetylation to acetoveratrone by acetic anhydride. Reaction conditions were evaluated with 15 wt.%TPA/22.4 wt:%ZrO2/MCM-41 calcined at 1123 K to get higher conversion of acetic anhydride to acetoveratrone. The reaction was found to be heterogeneously catalyzed and no contribution from homogeneous (leached) TPA into the medium under the reaction conditions. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: acetoveratrone; acetylation; MCM-41; TPA/ZrO2; veratrole

Alkene epoxidation catalyzed by vanadomolybdophosphoric acids supported on hydrated titania - Ingle, Rohit H.; Vinu, A.; Halligudi, Shivaraj B. (Catalysis Communications, 2008)
Vanadomolybdophosphoric acids wet-impregnated oil hydrated titania (TiO(2) - xH(2)O), make ail efficient catalytic system for the epoxidation of a variety of alkenes with organic solvent extracted TBHP as the oxidant. By,in appropriate choice of solvent, the catalyst call be reused at least three times without much loss in the activity for subsequent runs. XRD shows that the heteropoly acid is uniformly dispersed over the support and up to 15 wt% loading of the heteropoly acid, no additional peak of the same call be seen in the XRD pattern of the catalyst. The reactivity varied with the nature of alkene but the major product was always the corresponding epoxide. The catalytic system is free of high temperature calcination steps and tedious multi-step procedures, normally encountered in the heter-ogenization of heteropoly acids. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: alkenes; epoxidation; heteropoly acids; TBHP; titania; vanadomolybdophosphoric acids

Chemoselective synthesis of beta-amino acid derivatives by hydroamination of activated olefins using AISBA-15 catalyst prepared by post-synthetic treatment - Shanbhag, Ganapati V.; Kumbar, S. M.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2008)
beta-Amino acid derivatives have a wide variety of applications viz. in the synthesis of peptide analogues, precursor for amino alcohols, optically active amino acids, lactums and diamines. Chemoselective anti-Markovnikov hydroamination reaction of activated olefins was effectively used to synthesize beta-amino acid derivatives using AlSBA-15 and AlMCM-41 catalysts. These catalysts with different Si/Al ratios were synthesized by isomorphous substitution of aluminium into the framework of SBA-15, which induces the Bronsted and Lewis acid sites. The structural integrity of the catalysts was established by characterizing with XRD, N-2-sorption, TEM, NH3-TPD Al-27 MAS NMR and Si-29 MAS NMR techniques. Hydroamination of ethyl acrylate with aniline was used as a test reaction, which gave N-[2-(ethoxycarbonyl)ethyl] aniline with high selectivity. The performance of AlSBA-15 catalyst was also determined with different acrylates and amines to know the general applicability of the catalyst in hydroamination reactions. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: acrylate; activated olefin; addition; AlMCM-41; AlSBA-15; Amine; beta-amino acid; Catalyst; hydroamination; Mesoporous

Chiral Mn(III) salen complex immobilized onto ionic liquid modified mesoporous silica for oxidative kinetic resolution of secondary alcohols - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Tetrahedron Letters, 2008)
A supported ionic liquid strategy has been applied for the immobilization of a chiral Mn(III) salen complex onto ionic liquid modified mesoporous silica SBA-15. The immobilized catalyst demonstrated high enantioselectivity and activity in the oxidative kinetic resolution of secondary alcohols, and could be recycled five times without obvious loss of activity. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Mesoporous silica SBA-15; Mn(III) salen; Oxidative kinetic resolution; Secondary alcohol; Supported ionic liquid

Enantioselective hydrogenation of olefins by chiral iridium phosphorothioite complex covalently anchored on mesoporous silica - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2008)
Chiral monodentate phosphorous-based ligands have proven effective for the enantioselective hydrogenation of olefins. Binol-derived monodentate phosphorothioite (PS) ligand was synthesized from binol and thiopropyltriethoxysilane, and its iridium complex was covalently anchored to mesoporous silica supports like SBA-15, MCM-41, and MCM-48. These catalysts were characterized by different physicochemical techniques and assessed for their catalytic performances in the heterogeneous asymmetric hydrogenation of itaconic acid and its derivatives. It was found that the catalytic activities and enantioselectivities of the heterogenized iridium complex (IrPSSBA-15) in the hydrogenation reactions were comparable to its homogeneous analogue. Binol-derived monodentate phosphorothioite ligand in heterogeneously anchored form (iridium complex) is a more effective catalyst than the reported monodentate phosphorous ligand systems in the hydrogenation reactions, possibly due to the changes in electronic properties around the iridium metal center. The effects of substrate-to-catalyst molar ratio, solvents, and temperature on substrate conversions and enantioselectivities, of the products were investigated in hydrogenation reactions. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: binol; Enantioselective hydrogenation; Immobilization; iridium complex; itaconic acid; Mesoporous silica SBA-15; monodentate ligand; phosphorothioite ligand

Heteropoly acid-based supported ionic liquid-phase catalyst for the selective oxidation of alcohols - Bordoloi, Ankur; Sahoo, Suman; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2008)
A supported ionic liquid strategy has been applied for the immobilization of a heteropolyacid, molybdovanadophosphoric acid, onto ionic liquid-modified mesoporous silica SBA-15. The immobilized catalyst demonstrated high activity in the aerobic oxidation of primary and secondary alcohols to aldehydes and ketones, respectively. No overoxidation of the primary alcohols to carboxylic acids was observed. Secondary alcohols were chemoselectively oxidized to ketones in the presence of primary alcohol, hetero atom, and allyl groups. This catalyst could be recycled five times without obvious loss of activity. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Air as an oxidant; Mesoporous silica SBA-15; Molybdovanadophosphoric acid; Selective oxidation; Supported ionic liquid

Highly efficient and chemo selective catalyst system for the synthesis of blossom orange fragrance and flavoring compounds - Justus, Josena; Vinu, Ajayan; Devassy, Biju M.; Balasubramanian, Veerappan V.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Catalysis Communications, 2008)
{Acetal and acylal formation reactions of organic compounds are efficiently catalyzed by zirconia-supported mixed oxide systems under liquid-phase reaction conditions. 15WZ-750 (where
Keywords: Acetal; acylal; Silicotungstic acid; tungsten oxide; tungstophosphoric acid; Zirconia

Inorganic-organic hybrid materials based on functionalized silica and carbon: a comprehensive understanding toward the structural property and catalytic activity difference over mesoporous silica and carbon supports - Bordoloi, Ankur; Mathew, Nevin T.; Lefebvre, F.; Halligudi, Shivaraj B. (Microporous and Mesoporous Materials, 2008)
Inorganic-organic hybrid materials based on functionalized silica and carbon were synthesized by anchoring molybdovanadophosphoric acid (H-5[PMo10V2O40]center dot 32.5H(2)O) onto amine-functionalized SBA-15, ethane-bridged SBA-15 and mesoporous carbon, respectively. Small angle X-ray diffraction, N-2 sorption analysis, HRTEM, SEM, IFT-IR, CP-MAS NMR were used to diagnose the mesoporous structure of inorganic-organic hybrid materials. The structural integrity of molybdovanadophosphoric acid has been found to be retained after immobilization over mesoporous materials. These inorganic-organic hybrid materials were tested in the environmentally friendly oxidation of 2-methylnaphthalene (2MN) with 30%, aqueous hydrogen peroxide. Molybdovanadophosphoric acid containing mesoporous organosilica hybrid material (ethane-bridged SBA-15) exhibited higher catalytic activities in the oxidation of 2MN to give a clean product 2-methy-1,4-naphthoquinone (menadione vitamin K3 precursor), because of the improved hydrophobicity of the material. The correlation between structural properties and catalytic activities of these hybrid materials has been well addressed in our present studies. (c) 2008 Elsevier Inc. All rights reserved.
Keywords: 2-Methylnaphthalene; inorganic-organic hybrid materials; mesoporous carbon; mesoporous organosilica; Oxidation

Non-phosgene route for the synthesis of methyl phenyl carbamate using ordered AISBA-15 catalyst - Lucas, Nishita; Amrute, Amol P.; Palraj, K.; Shanbhag, G. V.; Vinu, Ajayan; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2008)
Methyl phenyl carbamate (MPC) has been synthesized Under liquid phase conditions from dimethyl carbonate and aniline by using mesoporous AISBA-15 catalyst. The catalyst with different Si/Al ratio was synthesized by isomorphous Substitution of aluminium into the framework of siliceous SBA-15. The structural integrity of the catalyst system was diagnosed with the help of various characterization techniques Such as X-ray diffraction, Surface analysis, and the acidity measurement has been done by TPD using ammonia as probe molecule. AISBA-15 (Si/Al = 10) exhibited highest catalytic activity in the synthesis of MPC under the reaction Conditions Studied. The effect of parameters Such as molar ratio of reactants, catalyst concentration. reaction temperature and time on the conversion of aniline was investigated. The results demonstrated that an aniline conversion of 99% and MPC selectivity of 71% were achieved when the reaction was carried out at 100 C, DMC to aniline mole ratio of 10 with 5% of catalyst (wt% of total reaction mixture) for 3 h. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: amines; Dimethyl carbonate; Mesoporous AISBA-15; Methoxycarbonylation; Methyl phenyl carbamate

[Ru(salen)(NO)] complex encapsulated in mesoporous SBA-16 as catalyst for hydrogenation of ketones - Bordoloi, Ankur; Amrute, Amol P.; Halligudi, Shivaraj B. (Catalysis Communications, 2008)
SBA-16 mesoporous silica with cubic lm3m structure was synthesized using Pluronic F127 poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock copolymer (EO106PO70EO106) and it blends with Pluronic P123 triblock copolymer (EO20PO70EO20) as supramolecular templates. The resulting material was used for encapsulating [Ru(salen)(NO)] complex and used in the hydrogenation of ketones to the corresponding alcohols. The pore entrance size of SBA-16 was precisely tailored by silylation with diphenyldichlorosilane to trap [Ru(salen)(NO)] complex in the cage of SBA-16. Small angle XRD, N-2 sorption measurements, UV-Vis and FT-IR analysis evidences the structural integrity of mesoporous silica as well as the complex. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Encapsulation; Hydrogenation; Ketones; SBA-16; [Ru(salen)(NO)] complex

Sol-gel synthesis of MoO(3)/SiO(2) composite for catalytic application in condensation of anisole with paraformaldehyde - Amrute, Amol P.; Bordoloi, Ankur; Lucas, Nishita; Palraj, K.; Halligudi, Shivaraj B. (Catalysis Letters, 2008)
MoO(3)/SiO(2) composite with varying amounts of MoO(3) loading (1-20 wt.%) were prepared by sol-gel method and calcined at 500 C. These catalysts were employed for the liquid phase condensation of anisole with paraformaldehyde. All the catalysts were characterized by N(2) sorption, XRD, and NH(3)-TPD. The activities of synthesized MoO(3)/SiO(2) catalysts were compared with p-toluene sulfonic acid (p-TSA), the most frequently used catalyst for the condensation reactions, and with a supported metal oxide (WO (x) /ZrO(2)). Under the similar reaction conditions, synthesized 10 wt.% MoO(3)/SiO(2) catalyst calcined at 500 C was found to be the most active in the condensation of anisole with paraformaldehyde.
Keywords: 4; 4'-Dimethoxydiphenylmethane; Condensation of anisole; MoO(3)/SiO(2) composites; Paraformaldehyde; Sol-gel synthesis

Studies in structural characterization and correlation with the catalytic activity of an efficient and stable WOx/SBA-15 nanocomposite catalyst - Bordoloi, Ankur; Halligudi, Shivaraj B. (Journal of Catalysis, 2008)
A new WOx/SBA-15 nanocomposite catalyst system was developed by hydrothermal synthesis. The material was characterized by X-ray diffraction, high-resolution transmission electron microscopy, sorption analysis, FT-IR, CP-MAS NMR, XPS, and energy-dispersive X-ray analysis. Various types of aromatic and aliphatic sulfides were selectively oxidized to sulfoxides in good to excellent yields without becoming overoxidized to the sulfones using 70% aq. tert-butyl hydrogen peroxide in the presence of nanocomposite catalyst at room temperature. The catalyst could be easily recovered and reused for at least eight reaction cycles under the reaction conditions described here with no significant loss of reactivity. (c) 2008 Elsevier Inc. All rights reserved.
Keywords: catalytic oxidation; mesoporous materials; Sulfides; Sulfoxides; tungsten oxide nanocluster

Synthesis of novel 2-alkyl substituted oleobenzimidazole derivatives using ethylene glycol as solvent - Hosamani, K. M.; Hiremath, V. B.; Keri, R. S.; Harisha, R. S.; Halligudi, Shivaraj B. (Canadian Journal of Chemistry-Revue Canadienne De Chimie, 2008)
The objective of this research was to conduct constructive organic chemistry by using ethylene glycol as an efficient solvent and to achieve yields that were comparable to or better than those in other media. The reaction parameters, such as temperature (150-200 degrees C), density, and reaction time (6 h), have been systematically studied to understand whether ethylene glycol is as an efficient solvent and can have a positive effect on the chemistry with good yields. By tuning the parameters, the yields have been optimized to around 70%-80%. Thus, a new class of 2-alkyl substituted oleo-benzimidazole derivatives have been synthesized and characterized by FTIR, (1)H NMR, (13)C NMR, MS, and elemental analysis.
Keywords: ethylene glycol; oleo-benzimidazole derivatives; oleochemistry; unusual fatty acids

Titania supported silicotungstic acid: an efficient solid acid catalyst for veratrole acylation - Waghmare, Nilesh G.; Kasinathan, Palraj; Amrute, Amol P.; Lucas, Nishita; Halligudi, Shivaraj B. (Catalysis Communications, 2008)
Titania supported silicotungstic acid (STA) with different STA loading (10-25 wt%) and calcination temperature (650-750 degrees C) were prepared by wet impregnation method. The catalysts have been represented by a general formula xSTiO(2)y (where x denotes wt%, S denotes STA and y denotes calcination temperature in degrees C). These catalysts were characterized by techniques such as X-ray diffraction, surface analysis, FTIR-pyridine and TPD-NH(3) and were used as heterogeneous solid acid catalysts in the liquid phase acylation of veratrole with acetic anhydride (Ac(2)O). It was found that 20STiO(2)700 gave the highest activity in acylation reaction due to its highest acidity. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: acetic anhydride; Acylation; Silicotungstic acid; titania; veratrole

Comparative study on liquid phase alkylation of 2-methylnaphthalene with long chain olefins using different solid acid catalysts - Lucas, Nishita; Bordoloi, Ankur; Amrute, Amol P.; Kasinathan, Palraj; Vinu, Ajayan; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Applied Catalysis A-General, 2009)
A comparative study has been made over a variety of solid acid catalysts, which include isopoly and heteropoly ions supported on various supports such as zirconia, titania, a large variety of zeolites and a couple of mesoporous materials for liquid phasealkylation of 2-methylnaphthalene with 1-octene.All the catalyst systems were characterized by nitrogen sorption analysis, X-ray diffraction and NH(3)-TPD. Inspite of their high acid amounts zeolites gave poor catalytic performance due to their diffusional constraints; on the other hand mesoporous materials lacked diffusional constraints but due to their low acid amounts resulted in poor conversions. lsopoly and heteropoly ions supported on zirconia and titania were found to be catalytically active for the reaction due to total surface acidity. Among them, isopolytungstate supported on zirconia exhibited the best catalytic activity and was used for further optimization of reaction conditions. Excellent conversions of all olefins (>92%) with high selectivity of monoalkylmethylnaphthalene (>95%) was obtained under optimized reaction conditions. The catalyst could be recycled for several times without any obvious loss of its activity. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: 2-Methylnaphthalene; Alkylation; Long chain olefins; Zirconia

Mesoporous silica immobilized cobalt complex: an efficient catalyst for epoxides ring opening by aromatic amines under ambient conditions - Bordoloi, Ankur; Hwang, Young Kyu; Hwang, Jin-Soo; Halligudi, Shivaraj B. (Catalysis Communications, 2009)
{Cobalt complex, CobpbH(2)Cl(2)2H(2)O [where
Keywords: beta-Amino alcohols; CobpbH(2)Cl(2)2H(2)O complex; Epoxide ring opening; Immobilization; SBA-15

Oxidative kinetic resolution of alcohols using chiral Mn-salen complex immobilized onto ionic liquid modified silica - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Applied Catalysis A-General, 2009)
The supported ionic liquid strategy has been applied for the immobilization of chiral Mn(III) salen complex onto ionic liquid modified silica. Chiral Mn(III) salen complex was immobilized over silica through a thin film of covalently anchored imidazolium ionic liquid. These catalysts were characterized by N(2) sorption, XRD, MR, DRUV-vis, and elemental analysis. The results showed that the chiral Mn(III) salen complex could be successfully immobilized onto the modified mesoporous materials and that the long-range mesoporous ordering of parent supports was maintained after the immobilization. The immobilized catalyst provided good enantioselectivity and activity in the heterogeneous catalysis of the oxidative kinetic resolution of secondary alcohol and can be recovered and recycled for four times without obvious loss of enantioselectivity and activity. Oxidative kinetic resolutions of meso-diols, hydroxyl ester and primary alcohol were also studied using this catalyst system. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Mesoporous silica; Mn(III) salen; Oxidative kinetic resolution; Secondary alcohol; Supported ionic liquid

Synthesis and characterization of novel schiff base polyurethanes - Raghu, A. V.; Gadaginamath, G. S.; Jeong, Han Mo; Mathew, Nevin T.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2009)
Eight different types of novel polyurethanes (PUs) were synthesized through the polyaddition reaction of 4,4'-(ethane-1,2-diylidenedinitrilo)diphenol and 4,4'(pentane-1,5-diylidenedinitrilo)diphenol with four different diisocyanates: 4,4'-diphenylmethane diisocyanate, toluene 2,4-diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate. The resulting PUs were soluble in polar, aprotic solvents. Structures of the diols and PUs were established with Ultraviolet-visible, fluorescence, Fourier transform infrared (FTIR), (1)H-NMR, and (13)C-NMR spectroscopy data. FTIR and NMR spectral data indicated the disappearance of both hydroxyl and isocyanate groups in the PUs. The thermal properties were investigated with thermogravimetry and differential scanning calorimetry. The weight losses, glass transitions, onset temperatures, and crystalline melting temperatures were measured. All the PUs exhibited semicrystalline and amorphous morphologies, as indicated by X-ray diffraction. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 113: 2747-2754, 2009
Keywords: amorphous; Morphology; polyurethanes; synthesis; Thermal properties

Synthesis of chiral sulfoxides by enantioselective sulfide oxidation and subsequent oxidative kinetic resolution using immobilized Ti-binol complex - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2009)
Chiral Ti-binol complex was immobilized onto ionic liquid modified SBA-15 and characterized by different physicochemical techniques. The catalyst was found to be highly enantioselective in the heterogeneous asymmetric oxidation of prochiral sulfides to sulfoxides and subsequent oxidative kinetic resolution of the sulfoxides using aqueous tert-butylhydroperoxide as the oxidant. A positive non-linear effect was observed in the oxidation-kinetic resolution of thioanisole using this supported catalyst. The supported catalyst was reused in multiple catalytic runs without any loss of enantioselectivity. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Kinetic resolution; Mesoporous silica; Non-linear effect; Sulfides; Sulfoxides; Supported ionic liquid; Ti-binol

Ordered mesoporous silica as supports in the heterogeneous asymmetric catalysis - Sahoo, Suman; Bordoloi, Ankur; Halligudi, Shivaraj B. (Catalysis Surveys from Asia, 2011)
Enantioselective synthesis of organic compounds has been studied by homogeneous catalysts for several years. However, these catalysts have yet to make a significant impact on industrial scales for fine chemical synthesis. A primary reason is the designing of a homogeneous asymmetric catalyst, which requires relatively bulky ligands and catalyst recovery and recycling often causes problems. One of the convincing ways to overcome this problem is to immobilise the asymmetric catalyst onto a solid support and the resulting heterogeneous asymmetric catalyst system can, in principle, be readily re-used. A large number of supports such as inorganic oxides including zeolites, alumina, zirconia, silica and organic polymers have been employed as supports in heterogeneous asymmetric catalysis. Therefore, in this review article we have summarized the work done by us in our laboratory on the immobilization of chiral transition metal complexes such as Ru, Ir, Mn and Ti onto ordered mesoporous silica and its asymmetric catalysis. All these immobilized catalysts were well characterized by different physicochemical techniques to confirm the structural retention of the support as well as the active metal complex after immobilization. This report includes our asymmetric catalytic investigations in enantioselective reactions such as hydrogenation of ketones, olefins, oxidation of sulfides and oxidative kinetic resolution of alcohols and sulfoxides through immobilized heterogeneous catalyst systems.
Keywords: Enantioselective hydrogenation; Enantioselective oxidation; Immobilization; Mesoporous silica; Oxidative kinetic resolution